Abdominal Drainage at Appendectomy for Complicated Appendicitis in Children: A Propensity-matched Comparative Study. Issue 6 (December 2021) - Fujishiro, Jun; Fujiogi, Michimasa; Hirahara, Norimichi; Terui, Keita; Okamoto, Tatsuya; Watanabe, Eiichiro; Ishimaru, Tetsuya; Miyata, Hiroaki
Abstract : Objective: The aim of the study was to investigate the effect of abdominal drainage at appendectomy for complicated appendicitis in children. Summary of Background Data: Although an abdominal drain placement at appendectomy is an option for reducing or preventing postoperative infectious complication, there is controversy regarding its effect for complicated appendicitis. Method: The study used the data on appendectomies for complicated appendicitis in children (⩽15 years old) that were operated in 2015 and registered in the National Clinical Database, a nationwide surgical database in Japan. One-to-two propensity score matching was performed to compare postoperative outcomes between patients with and without drainage at appendectomy. Result: The study included 1762 pediatric appendectomies for complicated appendicitis, 458 of which underwent abdominal drainage at appendectomy. In the propensity-matched analysis, the drainage group showed a significant increase in wound dehiscence [drain (−) vs drain (+); 0.3% vs 2.4%, P = 0.001], and postoperative hospital stay (median: 7 days vs 9 days, P < 0.001). There were no significant differences in the incidence of any complications, organ space surgical site infection, re-admission, and reoperation. Subgroup analyses in perforated appendicitis and perforated appendicitis with abscess, and open and laparoscopic appendectomy all demonstrated that drain placement was not associated with a reduction in any complication or organ space surgical site infection. However, it was significantly associated with longer hospital stays. Conclusion: This study suggested that an abdominal drain placement at appendectomy for complicated appendicitis among children has no advantage and can be harmful for preventing postoperative complications.